2018
DOI: 10.1002/job.2342
|View full text |Cite
|
Sign up to set email alerts
|

Are followers satisfied with conscientious leaders? The moderating influence of leader role authenticity

Abstract: Summary Leadership scholars have yet to identify a clear and consistent relationship between leader conscientiousness and followers' satisfaction with a leader. Drawing from socioanalytic theory and related personality research, we argue that the underlying motives of leader conscientiousness can manifest in systematically different behaviors aimed at team task accomplishment, ranging from rigid and order‐driven to relatively more adaptable approaches. Importantly, we posit that the relationship between a lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…However, Organ and Lingl (1995) indicated that the connection between conscientiousness and satisfaction is not always obvious as they found that conscientiousness was a negative predictor of co-worker satisfaction. In the context of leader-follower relationships, Harris et al (2019) found that conscientious leaders are usually more rigid, i.e. less adaptable, which, in turn, elicits less satisfaction from followers.…”
Section: Conscientiousness and Consumer Satisfactionmentioning
confidence: 99%
“…However, Organ and Lingl (1995) indicated that the connection between conscientiousness and satisfaction is not always obvious as they found that conscientiousness was a negative predictor of co-worker satisfaction. In the context of leader-follower relationships, Harris et al (2019) found that conscientious leaders are usually more rigid, i.e. less adaptable, which, in turn, elicits less satisfaction from followers.…”
Section: Conscientiousness and Consumer Satisfactionmentioning
confidence: 99%
“…In doing so, we randomly divided the peer ratings for a focal member into two groups (if more than one peer rating was available, as was the case for about 93% of the participants). Subsequently, we used responses from the first group to assess the focal member's initiating structure and consideration, whereas we used responses from the second group to assess his or her informal leader emergence (for similar procedures, see Harris et al, 2019; Ou et al, 2014). This approach was justified because interrater reliability and agreement statistics, as reported before, showed that peer ratings for a focal member were highly similar and, thus, largely interchangeable (Ostroff et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Conscientiousness has previously been shown to be one of the single biggest predictors of leadership success (Teodorescu et al, 2017). However recent research has shown that the positive impact of conscientiousness could be negated by other leader attributes, which moderate the conscientiousness-performance relationship by altering the behavioural manifestation of conscientiousness (Harris et al, 2019). Additionally, Judge and Bono (2000) found that conscientiousness was not significantly predictive of transformational leadership, particularly after controlling for other Big 5 traits, arguing that highly conscientious leaders might hinder their success by failing to delegate and engage in overly close supervision.…”
Section: Traits Of Leader Emergence and Effectivenessmentioning
confidence: 99%
“…For instance, leader levels of Conscientiousness (i.e. tendencies to be orderly, forward planning, thorough, and achievement orientated; Goldberg, 1992) have been argued to have both positive and negative implications for leader effectiveness (Harris et al, 2019;Hogan & Hogan, 2001;Judge et al, 2009). Judge et al (2002) found certain traits to be predictive of emergence but not of effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation